2002
DOI: 10.1029/2001wr000502
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic modeling of flood peaks using the generalized extreme value distribution

Abstract: [1] The generalized extreme value (GEV) distribution is a standard tool for modeling flood peaks, both in annual maximum series (AMS) and in partial duration series (PDS). In this paper, combined maximum likelihood estimation (MLE) and L moment (LMOM) procedures are developed for estimating location, shape, and scale parameters of the GEV distribution. Particular attention is given to estimation of the shape parameter, which determines the ''thickness'' of the upper tail of the flood frequency distribution. Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
135
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 148 publications
(150 citation statements)
references
References 48 publications
4
135
1
2
Order By: Relevance
“…Previous studies (Morrison and Smith, 2002;Northrop, 2004;Lima and Lall 2010;Villarini et al, 2011aVillarini et al, , 2011d found that the location and scale parameters scale linearly in the log-log domain (power-law behaviour) when plotted against drainage area. The power-law coefficients from these studies ranged between 0.5 and 0.8.…”
Section: Extreme Value Distributions and Upper Tail Propertiesmentioning
confidence: 97%
See 3 more Smart Citations
“…Previous studies (Morrison and Smith, 2002;Northrop, 2004;Lima and Lall 2010;Villarini et al, 2011aVillarini et al, , 2011d found that the location and scale parameters scale linearly in the log-log domain (power-law behaviour) when plotted against drainage area. The power-law coefficients from these studies ranged between 0.5 and 0.8.…”
Section: Extreme Value Distributions and Upper Tail Propertiesmentioning
confidence: 97%
“…The GEV parameters are estimated by means of maximum likelihood estimators (refer to Hosking, 1990;Martins and Stedinger, 2000;Coles, 2001, Morrison andSmith, 2002 among others for a discussion about other estimation techniques). Because of possible non-stationarities in the data which would require time-varying GEV parameters, the GEV distribution is fit only to those stations without statistically significant abrupt and slowly varying changes.…”
Section: Generalised Extreme Value Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of the GEV distribution has gained widespread application in recent literature because of its flexibility and ability to capture the frequency of extremes (Martins and Stedinger, 2000;Morrison and Smith, 2002;Nadarajah and Shiau, 2005). The GEV is the generalized form of three commonly applied extreme value distributions: the Gumbel, the Frechet and the Weibull.…”
Section: Gev Distributionmentioning
confidence: 99%